2018
DOI: 10.1016/j.foodchem.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antifungal activity and potential anti-virulence evaluation of the Eugenia uniflora essential oil against Candida spp.

Abstract: The development of fungal resistance to antifungal drugs has been worsening over the years and as a result research on new antifungal agents derived from plants has intensified. Eugenia uniflora L. (pitanga) has been studied for its various biological actions. In this study the chemical composition and antifungal effects of the E. uniflora essential oil (EULEO) were investigated against Candida albicans (CA), Candida krusei (CK) and Candida tropicalis (CT) standard strains. The essential oil obtained through h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 20 publications
2
25
0
3
Order By: Relevance
“…Inhibition of virulence of C. albicans strains by natural products was also shown by other scientists, among them Santos et al [26], who evaluated the essential oil of Eugenia uniflora L. (Myrtaceae) and demonstrated that at concentrations of 8192 µg/mL there is inhibition of hyphal projection. Two other species also from the same family that have the ability to inhibit the virulence of C. albicans are Psidium brownianum Mart.…”
Section: Discussionsupporting
confidence: 59%
“…Inhibition of virulence of C. albicans strains by natural products was also shown by other scientists, among them Santos et al [26], who evaluated the essential oil of Eugenia uniflora L. (Myrtaceae) and demonstrated that at concentrations of 8192 µg/mL there is inhibition of hyphal projection. Two other species also from the same family that have the ability to inhibit the virulence of C. albicans are Psidium brownianum Mart.…”
Section: Discussionsupporting
confidence: 59%
“…Citronellol can exert a broad inhibitory activity against the formation of biofilm. In fact, it acts against the planktonic forms of different Gram-positive (Listeria monocytogenes, Staphylococcus aureus, Staphylococcus epidermidis) and Gramnegative species (E.coli, Pseudomonas aeruginosa), inhibiting their capability to form biofilm when used at percentage ranging between 3.5% and 7% wt [58,59]. However, the antibacterial effectiveness can vary depending not only on the EO but also on the bacteria.…”
Section: Essential Oilsmentioning
confidence: 99%
“…Gucwa et al [5] have recently reported the activity of EOs from Thymus vulgaris , Citrus limonum , Pelargonium graveolens , Cinnamomum cassia , Ocimum basilicum and Eugenia caryophyllus against 183 clinical isolates of C. albicans and 76 isolates of C. glabrata . The chemical composition and antifungal effects of the Eugenia uniflora EO were recently investigated against C. albicans , C. krusei and C. tropicalis standard strains [6].…”
Section: Introductionmentioning
confidence: 99%